Nuansa Sastra Melayu dan Tasawuf Modern Dalam Tafsir Al-Azhar - Muhammad Muslihin (Al Burhan: Jurnal Kajian Ilmu dan Pengembangan Budaya Al-Qur'an, 2019)
Nusantara Tafsir is a must be maintained treasures, as always. It’s source of historical record of the country. Tafsir al-Azhar is one of the most important literatures from Nusantara scholars’ works that should be put into an analytical studies in order to gain its meaningful values. This research explains background, style, Hamka biography and some related isues of the tafsir. This article uses critical-descriptive approach which concludes that besides so many locality found in statement, event, example, and so on; melayu language is dominantly used in this Tafsir; more ever, modern sufism is quite a lot there in, so that its interpretation is in humanity style (adabi ijtima’i). What Hamka has interpreted, out of what has been mention above, is a problem solver to his society, so it seem to be a life event or live history at that time and after.